Calculation of technological parameters of deposition process of carbon films on copper buffer layer - Мansurov B. Z.; Мedyanova B. S.; Mansurova, M. E.; Аliyev B. A. (Recent Contributions to Physics, 2013)
In work calculations results of analytical dependences of technological parameters of deposition process of carbon films on copper buffer layer are presented, which allow to predict optimal concentration of hydrogen in a gas mix, intervals of working tension target-anode, thickness of deposited films and respectively time of experiments.